The effect of a dispersing agent on the properties of polypropylene composites with seaweed fillers - DEHANE, Aicha (Biopolymer Applications Journal, 2023)
The main focus of this work is to study the processability and characteristics of highly algae-loaded thermoplastic polymer composites. The seaweed powder was characterized in terms of morphology. Polymer/Alg composites were prepared by extrusion compounding. Polypropylene (PP) was used as the polymer matrix. During extrusion mixing, the composites were injection molded and characterized for their structural, morphological, and mechanical properties to determine the effect of the dipersent agent. The results for this research work has shown that algae can be used as a filler in the preparation of composites and that it is possible to play on the rate of the charge and of the dispersing agent to improve certain targeted properties for any specific application